2020
DOI: 10.1177/0897190020977730
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Managing Pharmacy Experiential Education During COVID-19

Abstract: In recent months, the coronavirus pandemic has significantly affected almost every industry in the United States, including health care and higher education. Faculty and students at colleges and schools of pharmacy nationwide have needed to quickly adapt as the delivery of curricula has shifted to primarily online format. Additionally, experiential rotations have been significantly affected as practice settings such as hospitals and outpatient clinics have limited students’ interactions with patients or stoppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…In the current COVID-19 environment, we are just starting to see published examples of pharmacy practice and education effects and response. 16,17,20,[23][24][25][26][27] However, there are a few public health APPE examples that have been published in the literature that describe similar rotation experiences. Patterson described an APPE in public health that was conducted at a free clinic that involved direct patient care, written assignments, role play and student discussions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current COVID-19 environment, we are just starting to see published examples of pharmacy practice and education effects and response. 16,17,20,[23][24][25][26][27] However, there are a few public health APPE examples that have been published in the literature that describe similar rotation experiences. Patterson described an APPE in public health that was conducted at a free clinic that involved direct patient care, written assignments, role play and student discussions.…”
Section: Discussionmentioning
confidence: 99%
“…19 Many colleges reported that students were allowed to work remotely and complete their APPEs by communicating with a preceptor and providing patient care via telephone, videoconferencing, and virtual access to patient charts. 17,20 Unfortunately, there were still many students who were unable to be consistently placed on required and elective experiential rotations, forcing colleges to find innovative solutions in order to keep students on track for graduation. For example, at our institution, over half of the APPE students were displaced (52% in April and 69% in May) from their originally scheduled rotations in the late spring of 2020.…”
Section: Introductionmentioning
confidence: 99%
“…If the project is describing changes made to an experience or discussing high-level considerations for restructuring or delivering learning experiences through telehealth, it may not require formal IRB approval, but it may be prudent to check with the local IRB before starting the project. 14…”
Section: Defining Plans For Research or Quality Assessment Projects Regarding Learner Involvement In Pharmacy Telehealth Practicementioning
confidence: 99%
“…The hospitals that provided this training were often located in the areas that were most severely affected by the pandemic and were unable to continue onsite training for students because of COVID-19 regulations. However, to allow pharmacy students to complete their internships, some units allowed their students to transition to online/virtual internships, while others provided a hybrid of physical and virtual internships, which enabled their students to practice remotely as well as engage in face-to-face learning and discussions with teachers at the hospital [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%